Building a Software Service for Mobile Devices to Enhance Awareness in Web Collaboration - Caballe, Santi; Xhafa, Fatos; Raya, Jordi; Barolli, Leonard; Uchida, Kazunori (2014 International Conference on Intelligent Networking and Collaborative Systems, 2014)
In this paper, we propose the construction of an effective event notification software service for mobile devices to provide anytime anywhere awareness to online work teams during Web collaboration. The software service is first designed to achieve the required flexibility to be used in different collaborative work situations, from professional work to informal communities of practice. Then, the building of our event-oriented service for mobile clients is reported from all the stages of our software engineering methodology and it is prototyped for evaluation purposes. We believe the outcomes of our approach will be very beneficial for achieving more productive and quality Web collaboration practices. The ultimate aim of this research is to provide software designers of Web collaboration tools and applications with general guidelines as for how to face common issues and challenges when incorporating a complete event management and notification system in their developments.